Post-Burn Psychosocial Outcomes in Pediatric Minority Patients in the United States: An Observational Cohort Burn Model System Study - Paul Won; Li Ding; Kara McMullen; Haig A. Yenikomshian (MDPI AG, 2023)
Racial and ethnic minority burn patients face barriers to longitudinal psychosocial support after injury. Studies utilizing the Burn Model System (BMS) National Database report adult minority patients experience worse psychosocial outcomes in domains such as body image during burn recovery. No study to date has investigated disparities in psychosocial outcomes by racial or ethnic category in the pediatric population using the BMS database. This observational cohort study addresses this gap and examines seven psychosocial outcomes (levels of anger, sadness, depression, anxiety, fatigue, peer relationships, and pain) in pediatric burn patients. The BMS database is a national collection of burn patient outcomes from four centers in the United States. BMS outcomes collected were analyzed using multi-level, linear mixed effects regression modeling to examine associations between race/ethnicity and outcomes at discharge after index hospitalization, and 6- and 12-months post-injury. A total of 275 pediatric patients were included, of which 199 (72.3%) were Hispanic. After burn injury, of which the total body surface area was significantly associated with racial/ethnicity category (p < 0.01), minority patients more often reported higher levels of sadness, fatigue, and pain interference and lower levels of peer relationships compared to Non-Hispanic, White patients, although no significant differences existed. Black patients reported significantly increased sadness at six months (β = 9.31, p = 0.02) compared to discharge. Following burn injury, adult minority patients report significantly worse psychosocial outcomes than non-minority patients. However, these differences are less profound in pediatric populations. Further investigation is needed to understand why this change happens as individuals become adults.